Latent heat thermal energy storage for solar water heating using flat heat pipes and aluminum fins as heat transfer enhancers - Malan, Daniel Johannes (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng) -- Stellenbosch University, 2014.